1997
DOI: 10.1111/j.1540-8159.1997.tb03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Venous Obstruction in Children with Transvenous Pacing Leads

Abstract: To determine the incidence and risk factors for venous obstruction in children with transvenous pacing leads, 63 children were evaluated clinically and echocardiographically. Patients with abnormal clinical and/or echocardiographic findings were further investigated by venography. Thirteen patients (21%) had evidence of venous obstruction. Venography in 11 (2 refused) showed that severity of obstruction (as defined by percentage of luminal narrowing) was complete (100%) in 3, severe (> 90%) in 4, and moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 16 publications
0
101
1
1
Order By: Relevance
“…Data are inconclusive for showing that anticoagulation prevents thrombosis in these patients. Figa et al 536 reviewed risk factors for venous obstruction in pediatric patients with transvenous leads. A cross-sectional pacemaker lead area of >6.6 mm 2 /m 2 body surface area increases the risk for thrombosis.…”
Section: Pacemakers and Internal Cardiac Defibrillatorsmentioning
confidence: 99%
“…Data are inconclusive for showing that anticoagulation prevents thrombosis in these patients. Figa et al 536 reviewed risk factors for venous obstruction in pediatric patients with transvenous leads. A cross-sectional pacemaker lead area of >6.6 mm 2 /m 2 body surface area increases the risk for thrombosis.…”
Section: Pacemakers and Internal Cardiac Defibrillatorsmentioning
confidence: 99%
“…10 Figa et al showed in children that the main risk factor for obstruction was found to be related to the total cross-sectional area of the lead as compared with the body surface area at implantation. 11 A ratio >6.6 mm 2 /m 2 was found to best predict venous obstruction. When selecting the pacemaker the leads, the use of an active-fixation lead seems preferable to a passive-fixation lead, given the abnormal positioning of the atrial lead in a systemic venous baffle and the placement in the nontrabeculated morphological left ventricle.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…A recent study showed that patient age, body size, and lead characteristics at implant did not clearly predict venous occlusion (Bar-Cohen et al, 2006). However, an earlier study concluded that if the lead size indexed to body surface area was more than 6.6 mm2/m2, venous thrombosis could be predicted with a sensitivity of 90% and specificity of 84% (Figa et al, 1997). The recent development of a lumenless 4.1 F endocardial lead is a promising new lead design, which may decrease the risk for venous occlusion in children (Chakrabarti et al, 2009).…”
Section: Endocardial or Epicardial Pacing System?mentioning
confidence: 99%
“…The concern of venous patency in children who need life-long pacing has been an argument for a more conservative approach of selecting a lead system, preferring the epicardial approach (Bracke et al, 2003;Bar-Cohen et al, 2006). Complete venous obstruction has been documented in 11 -21% of children at medium-term follow-up (Bar- Cohen et al, 2006;Figa et al 1997, Kammeraad et al, 2004. Partial venous obstruction may be seen in another 12% of children receiving an endocardial pacing system Fig.…”
Section: Endocardial or Epicardial Pacing System?mentioning
confidence: 99%